Análise do efeito de entropia em computação quântica: simulações em ambiente paralelo - Moretti, Rafael Henrique [UNESP] (2015)
The increasing technological development has brought great bene ts to humanity, in several areas. In order to continue this development, new research areas are emerging to reach new technologies. The physical limits of classical computing, based on electromagnetic phenomena are being achieved and quantum computing emerges as a possible solution to these limits, as well as to introduce a new scenario for computing, due to its great potential. In order to get a better understanding of phenomena involving quantum computing in a data transmission, in particular the phenomenon of entanglement, this work presents a theoretical quantum mechanics, information, computing and quantum entropies, as well as parallel computing and MPI, proposing a simulation with implementation in parallel environment on the e ect of the entropy of entanglement of photons in data transmission and comparison with implementation in a single processor environment